Theory of symmetric winding distributions and a general method for winding MMF harmonic analysis. Issue 13 (26th January 2021) - Sun, Yi; Lin, Yingqian; Wang, Yunchong; Nilssen, Robert; Shen, Jian‐Xin
Abstract : One of the main challenges in motor design is the winding layout, including winding distributions and magnetomotive force (MMF) harmonic analysis. Considering some shortcomings in the existing theories for winding distributions and difficulties in dealing with unconventional fractional‐slot windings, a unified theory of symmetric winding distributions is proposed. First, this study gives the sufficient and necessary conditions for a m ‐phase symmetric winding and the novel winding distribution formula. Subsequently, a general method for MMF harmonic analysis including the amplitude of MMF harmonics and harmonic orders are proposed. Finally, the analysis results show that this unified theory is an efficient and compact method to deal with the winding layout to analyse all kinds of winding MMF harmonics.